Utilization of Galleries as Educational Spaces for Artistic Creation by Students - Esterica Yunianti; Nanang Yulianto (Universitas Sebelas Maret, 2024)
The art gallery serves as a space for the exhibition of art objects and creations, intended for appreciation. Typically, art galleries are often perceived as uninteresting and monotonous places, appealing only to a select audience. However, art galleries are not merely exhibition spaces; they can also serve as venues for communication, learning, workshops, discussions, and even artistic creation. Located in Clupak Mojopuro Sumberlawang Sragen, there is a residence that not only serves as a dwelling but also functions as an art gallery known as